DESIGNING VIRTUAL SPORT BASED ON METAVERSE GAMES AS A GREEN BUSINESS PROSPECT TO OVERCAME CIGARETTE ADDICTION - Al Mutasimbillah, Muhammad Rofi Ussan; Meilina, Restin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Cigarette addiction is a serious public health problem with negative impacts on individuals and the environment. An effort to address this issue, the design of virtual sports based on game platforms in the Metaverse has emerged as a promising solution. This study aims to explore this design as a sustainable green business prospect in combating cigarette addiction. The research was conducted using a qualitative research method. We interviewed a group of active smokers aged 17 to 25 years to understand their needs and preferences regarding alternatives to smoking. The results of the study showed that the majority of respondents had a strong desire to quit smoking and were actively seeking healthier alternatives. As a solution, we developed a design for virtual sports based on game platforms in the Metaverse. This media platform brings together active smokers to participate in virtual sports activities as a substitute for smoking. This design has the potential to be a sustainable green business prospect with a holistic approach to environmental management. It emphasizes the importance of providing attractive alternatives and fostering a supportive environment for individuals to overcome their addiction. Moreover, the design has the potential to be a successful green business venture that promotes both individual well-being and environmental sustainability.